Terms referring to psoriasis vulgaris in the classical Chinese medicine literature: a systematic analysis. (April 2016) - Zhang, Claire Shuiqing; May, Brian; Yan, Yuhong; Yu, Jason Jingjie; Yao, Danni; Chang, Suyueh; Zhang, Anthony Lin; Guo, Xinfeng; Lu, Chuanjian; Xue, Charlie Changli
Abstract: Background: Psoriasis vulgaris is a modern medical term. In the classical Chinese medicine (CM) literature, this disorder could be classified under a diversity of terms. In order to explore how psoriasis vulgaris was conceptualized and managed throughout Chinese medical history, we undertook a systematic longitudinal analysis of descriptions in the classical CM literature of skin disorders consistent with psoriasis vulgaris. Methods: Candidate search terms were identified from 33 contemporary CM books as relevant to psoriasis vulgaris. Thirteen terms were used to search the Zhong Hua Yi Dian —'Encyclopaedia of Traditional Chinese Medicine', 4th edition, a digital collection of over 1000 medical books. Search results were entered in a spreadsheet, citations that were consistent with psoriasis vulgaris were identified based on: (i) a description of the features of psoriasis vulgaris and (ii) judgment by two clinicians regarding relevance to psoriasis vulgaris. Analysis focused on the use of terms by historical period (Chinese dynasty) and whether the terms were specific for psoriasis vulgaris Results: 608 citations dating from 363 to 1947AD were included. The two criteria for determining inclusion of citations were combined to select the pool of citations most relevant to psoriasis vulgaris. Sixty citations from eight search terms were found in this pool. Among the eight terms, Bai Bi, She Shi and Bi Feng consistently identified citations that were likely to be psoriasis. The earliest was from 1368AD (Ming dynasty). The remaining five terms yielded inconsistent results. Citations of disorders consistent with psoriasis vulgaris appear prior to 1368–1644AD (Ming dynasty), but the terms used were not specific for psoriasis. Conclusions: Bai Bi, She Shi and Bi Feng are the terms most consistently used to refer to psoriasis vulgaris. They first appeared in 1368–1644AD (Ming dynasty) and Bai bi remains in use. Regarding the other terms, certain citations may have referred to psoriasis vulgaris, but in other cases these terms could be used for disorders whose descriptions were inconsistent with psoriasis.